High-capacity phase-sensitively amplified transmission in a field-deployed fiber cable - Zhirong Chen; Xiaojie Guo; Yingyu Chen; Yongguang Xiao; Jingshun Pan; Zhengyong Liu; Chao Lu; Zhaohui Li (Communications Engineering)
Abstract Phase-sensitive amplifiers (PSAs) outperform conventional phase-insensitive amplifiers by enhancing signal-to-noise ratio (SNR) through distinct gains for deterministic signal and stochastic noise depending on their phase features. Yet despite this potential, the practical implementation of PSAs in deployed fiber transmission systems remains under-explored. Here we present the field trial of high-capacity phase-sensitively amplified transmission in a field-deployed optical fiber cable. Same-wavelength bi-directional transmission of wavelength-division-multiplexing signals is utilized to increase the capacity in one fiber core. A wideband PSA based on periodically poled lithium niobate waveguides is demonstrated as a pre-amplifier at the receiver, which both increases the signal power and improves the SNR by mitigating the interference crosstalk primarily caused by Rayleigh backscattering along the fiber. A net transmission capacity of 10.944 Tb·s−1 and a net capacity-distance product of 541.728 Tb·s−1·km are achieved, which exceed the results of prior studies in phase-sensitively amplified transmission. These results confirm the favorable performance of PSA-based pre-amplification for large-capacity optical fiber transmission in real deployment.